Finding the Other Way - Lloyd George, Megan (Tufts Archival Research Center, 2006)
Liberal Member of Parliament for the Isle of Anglesey (1929-1951) and Deputy Leader of the British Liberal Party (1949-1951), Megan Lloyd George states how her generation, which grew up during WWI, has never known true peace, and describes her belief that one's perspective will never be quite accurate with a spiritual component.